2018
DOI: 10.3390/ijerph15061180
|View full text |Cite
|
Sign up to set email alerts
|

General Practice Care for Patients with Rare Diseases in Belgium. A Cross-Sectional Survey

Abstract: There are almost no studies about rare diseases in general practice. This study examined care characteristics of active rare disease patients in the Belgian Network of Sentinel General Practices (SGP) and the importance of rare diseases in general practice by its caseload, general practitioner (GP)–patient encounter frequency and nationwide prevalence. The SGP reported data about: (i) the number of active rare disease patients in 2015; and (ii) characteristics of one to three most recently seen patients. Rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…For 38% of patients their GP was involved in their diagnosis either by making the diagnosis directly or playing a major role in the diagnostic work up of the patient. This compares to a recent Belgian study which showed that, for 121 RD patients, 36% of the time the GP established the diagnostic referral [17].…”
Section: Discussioncontrasting
confidence: 76%
“…For 38% of patients their GP was involved in their diagnosis either by making the diagnosis directly or playing a major role in the diagnostic work up of the patient. This compares to a recent Belgian study which showed that, for 121 RD patients, 36% of the time the GP established the diagnostic referral [17].…”
Section: Discussioncontrasting
confidence: 76%
“…Similarly, it was shown that also in other countries, i.e. Belgium or Ireland, where GPs tend to be the first caregivers for RD patients, establish a diagnostic referral and have access to information resources on RDs, few physicians possess adequate knowledge on such diseases and rarely use Orphanet or other reliable sources on the Internet [ 26 , 27 ]. However, this research also shows that physicians are aware of the importance of RDs, as well as of their knowledge deficits and unpreparedness in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, there was a major mismatch between the recommendations of the 5 guidelines with the specific care context of the assessor. Thus, the medical needs both of treating physicians and patients must be explored and aligned with the guideline recommendations, as has been performed for other orphan conditions (Boffin et al 2018). Importantly, our evaluation did not evaluate the recommended therapies in the respective guideline but instead focused on their methodological quality.…”
Section: Discussionmentioning
confidence: 99%